2013
DOI: 10.1080/10288457.2013.826974
|View full text |Cite
|
Sign up to set email alerts
|

Mapping a Group of Northern Namibian Grade 12 Learners' Algebraic Non-routine Problem Solving Skills

Abstract: This article investigates the algebraic non-routine problem-solving skills of grade 12 learners of a high-achieving school in northern Namibia. The school was selected on the basis of its outstanding results and sound management style. The study followed a descriptive survey design that involved a written test to examine learners' problem-solving skills together with the solution strategies used, and structured learner interviews to get their views about the choice of strategies for solving non-routine problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Likewise, Webb [15] even pointed out that engaging learners into numerous cognitive processes augment their problem-solving abilities and understanding. Mathematics problem solving through non-routine problems plays a vital role in inculcating higher-order thinking skill that leads to the development of thinking and reasoning skills [16]. Besides, non-routine problems demand flexibility; it requires the knowledge of various problem-solving heuristics and strategies [17].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Webb [15] even pointed out that engaging learners into numerous cognitive processes augment their problem-solving abilities and understanding. Mathematics problem solving through non-routine problems plays a vital role in inculcating higher-order thinking skill that leads to the development of thinking and reasoning skills [16]. Besides, non-routine problems demand flexibility; it requires the knowledge of various problem-solving heuristics and strategies [17].…”
Section: Introductionmentioning
confidence: 99%
“…Non-routine problems are kinds of problems that require the use of different strategies and heuristics [9]. These problems are more difficult and complicated than routine problems because numerous approaches must be devised to solve an unfamiliar situation [10]. Thus, these problems require flexibility and strategic thinking to extend previous knowledge and concepts that allow having different pathways to a solution, leading to the enhancement of student's Mathematical creativity [11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Mogari and Lupahla (2013) found that Namibian learners most preferred the algebraic strategy to other strategies, even though they successfully solved problems that were illustrated with diagrams. The Filipino learners in Mabilangan, Limjap and Belecina (2011) used the 'making a model or diagram' strategy the most.…”
Section: Non-routine Mathematical Problem Solving Strategiesmentioning
confidence: 99%
“…Elia, van den Heuvel-Panhuizen and Kolovou (2013, p607) consider NRMPs 'more complicated and difficult than routine problems' and similarly, according to Mogari and Lupahla (2013, p95), they are 'more cognitively challenging and demanding than routine problems'. NRMPs are tasks based on real life circumstances or models thereof that cannot be solved using familiar methods by replicating known procedures (see Muis, 2004;Arslan & Altun, 2007;Mogari & Lupahla, 2013). To this end, in the view of Arslan and Altun, NRMP reflects the relationship between mathematics and reality.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation